CRIMINAL ACTS OF CORRUPTION (BRIBE) BY PRIVATE HOSPITAL AGAINST A MIDWIFE IN REWARD FOR SERVICES FOR PATIENT REFERRAL - sutrisno, achmad; Soekorini, Noenik (Universitas Islam Lamongan, 2023)
The term bribe in corruption cases is a bribe or money given to another party to facilitate certain goals. People in Indonesia refer to bribes as facilitation payments. Cases of bribery have been going on for a long time in Indonesia. Bribes are usually given to officials in the government bureaucracy who have important roles, law enforcers, as well as customs and tax officials. Ironically, cases of bribery are still considered common in Indonesia.The results of a survey at the